Attachment Theory and Maternal Drug Addiction: The Contribution to Parenting Interventions - Parolin, Micol; Simonelli, Alessandra (Frontiers in Psychiatry, 2016)
Children’s emotional and relational development can be negatively influenced by maternal substance abuse, particularly through a dysfunctional caregiving environment. Empirical evidence indicates that parenting is negatively influenced by maternal drug use and its associated adverse psychosocial conditions. As a consequence, many interventions have focused on enhancing parental skills, but they have often overlooked the emotional and relational features of the mother-infant bond. Instead, Attachment Theory offers a privileged framework to analyse how drug addiction can affect the quality of an adult’s attachment style, parenting attitudes and behaviours towards the child and can have a detrimental effect on the co-construction of the attachment bond by the mother and the infant. Several studies have also identified a prevalence of insecure patterns among drug-addicted mothers and their children, but a specific model of insecurity is still needed to be attested, requiring further investigations. In recent years, a number of protocols have been developed in order to strengthen the relationship between drug-abusing mothers and their children, drawing lessons from Attachment Theory. The present study reviews the literature on the adult and infant attachment style in the context of drug addiction, describing currently available treatment programs which address parenting and specifically focus on the mother-infant bond, relying on Attachment Theory.